Implementation of risk-based lipid-lowering therapies in older (age ≥ 65 years) and very-old adults (age ≥ 75 years) with ischemic heart disease in the greater Salzburg region - Kopp, Kristen; Motloch, Lukas J.; Wernly, Bernhard; Berezin, Alexander E.; Maringgele, Victoria; Dieplinger, Anna; Hoppe, Uta C.; Lichtenauer, Michael (Frontiers in Pharmacology, 2024)
Introduction: European guidelines recommend the implementation of lipid-lowering therapies (LLTs) in adults (≥ 65 years) with established atherosclerotic cardiovascular disease (ASCVD) and for risk-based primary prevention in older adults (≤ 75 years), yet their use in very-old adults (> 75 years) is controversial, discretionary, and oriented on the presence of risk factors. The aim of this retrospective study is to assess guideline-directed LLT implementation and low-density lipoprotein cholesterol (LDL-C) target achievement in high-/very-high-risk older/very-old adults (65–74 and ≥ 75 years) at presentation for ST-segment elevation myocardial infarction (STEMI) and also to assess evidence-based care delivery to older adults in our region. Methods: All STEMI patients with available LDL-C and total cholesterol presenting for treatment at a large tertiary center in Salzburg, Austria, 2018–2020, were screened (n = 910). High-risk/very-high-risk patients (n = 369) were classified according to European guidelines criteria and divided into cohorts by age: < 65 years (n = 152), 65–74 years (n = 104), and ≥ 75 years (n = 113). Results: Despite being at high-/very-high-risk, prior LLT use was < 40% in the total cohort, with no significant difference by age. Statin monotherapy predominated; 20%–23% of older/very-old adults in the entire cohort were using low-/moderate-intensity stains, 11%–13% were using high-intensity statins, 4% were on ezetimibe therapy, and none were taking proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. In the secondary prevention cohort, 53% of older/very-old patients used prior LLTs. Significantly higher percentages of older/oldest ASCVD patients (43% and 49%) met LDL-C targets < 70 mg/dL compared to patients < 65 years (29%; p = 0.033), although just 22% and 30% of these older groups attained stricter LDL-C targets of < 55 mg/dL. Low LLT uptake (16%) among older adults aged 64–74 years for primary prevention resulted in 17% and 10% attainment of risk-based LDL-C targets < 70 mg/dL and < 55 mg/dL, respectively. Oldest adults (≥ 75 years) in both primary and secondary prevention groups more often met risk-based targets than older and younger adults, despite predominantly receiving low-/moderate-intensity statin monotherapy. Conclusion: Secondary prevention was sub-optimal in our region. Less than half of older/very-old adults with established ASCVD met LDL-C targets at the time of STEMI, suggesting severe care-delivery deficits in LLT implementation. Shortcomings in initiation of risk-based LLTs were also observed among high-/very-high-risk primary prevention patients < 75 years, with the achievement of risk-based LDL-C targets in 10%–48% of these patients.